Limites e perspectivas do trabalho em equipe no programa saúde da família de Campina Grande PB: as representações sociais dos profissionais - Leite, Rosana Farias Batista (2007)
In Brazil, from 1994, the Health Department created the Health Family Program (HFP), being Campina Grande and other thirteen cities in Brazil the pioneer in the implantation of this proposal. The HFP is presented as a strategy for reorganization of the basic attention, aiming to change the assistant model of health. The program emphasizes, among others aspects, interdisciplinary actions with the objective to assure the accomplishment of the principles of the Unique System of Health. The present study has as main objective to analyze the social representations of the professionals about the work in the HFP of Campina Grande, Paraíba. The specific objectives are to analyze the limits and perspectives of this work verifying if there is interchange of knowledge pointed at the construction of a interdisciplinary work or if the fragmented daily work prevails. The research was development with bases on the Social Representations Theory, through the contributions of Serge Moscovici, for whom the social representations are understood as the common sense and practical knowledge elaborated by social group and transmitted by the social communication. It is a qualitative research that had as instruments to collect the data the half-structured interview and the participant comment, registered in the diary. 24 professionals were interviewed, of which 03 are doctors, 03 nurses, 04 aid nurses, 02 dentists surgeons, 02 social assistants, 09 health agents, and 01 assist of dental doctor's office. The analysis of the interviews was made based on the proposal of analysis of Thematic Content suggested by Bardin 1977. This research had three thematic groups: Representation of the HFP, Representation of the Work in HFP, Representation of the Work in Team and Interdisciplinary Work. For all people interviewed the HFP was represented as a program that brought positive contributions. The work in HFP is represented as a planned", "organized", and "rewarding" work. On the other hand, several speeches express non-satisfactions. The team work was represented as complemented work , as work between equals, respect the colleague´s space and as being with a family , being this last representation emphasized by the professionals of middle level, in a utopian and romantic vision. According to the interdisciplinary work it was highlighted the representations as changes of knowledge , dialogue and team of professional . The research points that the work in the HFP is represented as an acquaintance shared in the same physical space, indicating a boarding of different professionals without there is in fact the interdisciplinarity. The challenge that is present for the professionals remains, because there is no observation on the disruption with the traditional paradigm of the health, based, among others component, on the fragmentation and overlapping of the knowledge.